PENINGKATAN KINERJA KARYAWAN MELALUI PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL DAN PENGEMBANGAN KARIR KARYAWAN DI KIMIA FARMA (KLINIK DAN APOTEK) KOTA SERANG - Siti Masitoh; Khaeruman Khaeruman; Edi Muhammad Abduh (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The company has employees whose performance is quality to improve all activities within the company. The better the employee's performance, the better it is to increase the company's success. The purpose of this research is to determine partial or simultaneous improvement in employee performance through transformational leadership and employee career development. Using a causal associative type quantitative approach with saturated sampling where the sample was taken from the entire population of 47 respondents. Using SPSS version 26 for data analysis.The results of this research show that the transformational leadership variable has tcount > ttable or 4.329 > 2.015 and the significant value is 0.000 < 0.05. The Employee Career Development variable has a value of tcount < ttable or 9.738 > 2.015 and a significant value of 0.000 < 0.05. so it can be seen that the value of fcount > ftable or 85,545 > 3.21 and the significant value is 0.000 < 0.05. The coefficient of determination value was 79.5%, while the remaining 20.5% was an increase in other variables that were not explained in this study. So it is concluded that there is an increase in employee performance through transformational leadership and employee career development simultaneously and significantly.